Some Evaluation Questions - William Shadish (Practical Assessment, Research, and Evaluation, 1998)
Accessed 90,154 times on https://pareonline.net from November 13, 1999 to December 31, 2019. For downloads from January 1, 2020 forward, please click on the PlumX Metrics link to the right.
Keywords: Causal Models; Criteria; *Evaluation Methods; Evaluation Problems; Evaluation Utilization; *Evaluators; *Inferences; Performance Factors; *Program Evaluation; Qualitative Research; Standards; *Theory Practice Relationship; User Needs (Information)